Comorbidities and Risk Factors Associated with Inflammatory Vasculitis in the Adult Population - Ian Daniel Millstein; Arjun Kumar; Zachary Bishop; Angelo-Jesus Pingol; Kenyon Sprankle; Emily Ai; Richard Citta; Peter Coriell; Tabitha Jaison; Rahul Menon; Joseph Nowacki; Sonia Patel; et al. (Journal of Primary Care & Community Health)
Introduction/Objectives: Inflammatory vasculitis (IV) is characterized by blood vessel inflammation, leading to vessel damage and potential organ failure. This study aimed to identify the risk factors and comorbidities in adults with IV. Methods: A retrospective review of adult patients receiving outpatient care was conducted. Variables were compared between IV and non-IV (NoIV) groups. Results: Among 1500 patients, 626 (41.7%) had IV. Patients in the IV group were significantly older (IV = 66.5 ± 18.8 vs NoIV = 52.9 ± 18.4 years; P  < .001) and women (IV = 67.7 vs NoIV = 48.0%; P  < .001). IV group had a lower prevalence of patients of White race, and higher prevalences of use of tobacco and recreational drugs. Higher frequencies of associations of comorbid medical conditions were noted in the IV group compared to NoIV group, such as hypertension (50.7 vs 29.0%; P  < .001), DM (19.4 vs 10.4%; P  < .001), CKD (12.1 vs 3.7%; P  < .001), CAD (12.1 vs 6.2%; P  < .001), CHF (5.8 vs 2.0%; P  < .001), PAD (2.4 vs 0.8%; P  = .013), COPD (7.8 vs 1.8%; P  < .001), pulmonary fibrosis (2.4 vs 0.1%; P  < .001), osteoporosis (10.4 vs 1.9%; P  < .001), osteoarthritis (12.0 vs 7.1%; P  = .001), GERD (21.8 vs 13.2%; P  < .001), depression (14.1 vs 7.9%; P  < .001), hypothyroidism (14.2 vs 8.2%; P  < .001), anemia (16.9 vs 5.0%; P  < .001), seizure disorder (3.0 vs 0.9%; P  < .001), cancer (13.7 vs 8.5%; P  = .001), asthma (15.3 vs 6.7%; P  < .001), atrial fibrillation (9.6 vs 4.7%; P  < .001), CVA (7.0 vs 2.5%; P  < .001), SLE (2.9 vs 0.5%; P  < .001), and rheumatoid arthritis (5.0 vs 0.8%; P  < .001). There were significantly greater odds of IV with increasing age per year (OR 1.030, 95% CI 1.022-1.039; P  < .001), recreational drug use (OR 1.953, 95% CI 1.150-3.318; P  < .013), hypertension (OR 1.590, 95% CI 1.155-2.188; P  = .004), DM (OR 1.621, 95% CI 1.080-2.434; P  = .020), osteoarthritis-osteoporosis (OR 1.496, 95% CI 1.020-2.193; P  = .039), cardiac disorders (OR 1.543, 95% CI 1.065-2.236; P  = .022), pulmonary disorders (OR 3.173, 95% CI 1.663-6.054; P  < .001), and rheumatological disorders (OR 3.589, 95% CI 1.780-7.236; P  < .001). Conclusion: IV is associated with older age, female sex, non-White race, tobacco use, recreational drug use, hypertension, DM, cardiovascular disorders (CAD, CHF, PAD, CVA), pulmonary disorders (COPD, asthma, pulmonary fibrosis), osteoporosis, osteoarthritis, SLE, and rheumatoid arthritis.